1989
DOI: 10.1055/s-2006-961914
|View full text |Cite
|
Sign up to set email alerts
|

Hinokiflavone, a Cytotoxic Principle fromRhus succedaneaand the Cytotoxicity of the Related Biflavonoids1

Abstract: Hinokiflavone (1) was isolated as the cytotoxic principle from the drupes of Rhus succedanea L. A comparison of the cytotoxicity of 1 and other related biflavonoids, including amentoflavone (2), robustaflavone (3), agathisflavone (4), rhusflavone (5), rhusflavanone (6) and its hexaacetate (7), succedaneaflavanone (8) and its hexaacetate (9), cupressuflavone (10), neorhusflavanone (11), volkensiflavone (12) and its hexamethyl ether (13), spicataside (14) and its nonaacetate (15), morelloflavone (16) and its hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
4

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 3 publications
0
32
0
4
Order By: Relevance
“…wurden als Biflavonoide die Hinokiflavone ("Rhusflavone") und Bichalcone gefunden [29,34]. Letztere zeigen in vitro zytotoxische Wirkungen auf HT29-und HCT-146-Colontumor-Zelllinien [30,35].…”
Section: Biflavonoide (Tab 1 Tab 2b)unclassified
See 1 more Smart Citation
“…wurden als Biflavonoide die Hinokiflavone ("Rhusflavone") und Bichalcone gefunden [29,34]. Letztere zeigen in vitro zytotoxische Wirkungen auf HT29-und HCT-146-Colontumor-Zelllinien [30,35].…”
Section: Biflavonoide (Tab 1 Tab 2b)unclassified
“…Letztere zeigen in vitro zytotoxische Wirkungen auf HT29-und HCT-146-Colontumor-Zelllinien [30,35]. Hinokiflavone haben in vitro in starker Verdünnung ebenfalls antineoplastische Wirkung [29,46].…”
Section: Biflavonoide (Tab 1 Tab 2b)unclassified
“…A comparison of the cytotoxicity of 88 and other related biflavonoids indicates that an ether linkage between two units of apigenin as seen in 88 is structurally required for significant cytotoxicity (107).…”
Section: Alkaloids Kuafumine (60) Is a New Cytotoxic Alkaloid Frommentioning
confidence: 99%
“…1a, molecular formula C30H18O10) with high stability is extracted from Selaginella tamariscina, Juniperus phoenicea, Rhus succedanea, and several other plants and is commonly used in oriental medicines. [11][12][13] Hinokiflavone is a biflavonoid active constituent of flavonoids, a class of plant secondary metabolites, which have been reported to have multiple biological properties, including antioxidative, anti-inflammatory, antimicrobial, and antitumor. 12,[14][15][16][17] Theodoratou et al found strong and linear inverse associations between flavonoids and CRC risk by using data from a national prospective case-control study in Scotland.…”
Section: Introductionmentioning
confidence: 99%